Inovasi Pembelajaran Penyampaian Pesan-Pesan Al Qur’an kepada Anak melalui Roadshow Berkisah Islami (Participatory Action Research) - Rahwamati, Lilis; Nurul Fuad (Bisma : Bimbingan Swadaya Masyarakat, 2024)
With the teaching of the Quran at an early age will serve to provide a learning experience to the child, but more importantly serve to shape the personality or behavior of the child. Childhood is a great opportunity to establish religious control, so that the child can know which things are forbidden in religion and which are allowed. More than that, childhood also greatly determines the process of forming individual and social morals. The method used is PAR (Participatory Action Research). The results of the assistance showed that the delivery of the contents of the Quran to children with interesting methods so that the child will be easier to absorb and not feel in the teacher.